Economic Aspects of Tourist Regions - Zmyślony, Piotr (Turyzm/Tourism, 2003)
The article, based on research conducted over the last 35 years, presents the concept of a tourist region as a spatial economic unit. The method of categorising a tourist region is analogous to categorising tourist space as a type of general space. The author also points out possible applications of the conclusions of the analysis, as well as its usefulness in the future study of regional aspects of tourism.